Effect of repeated invitations on uptake of colorectal cancer screening using faecal occult blood testing: analysis of prevalence and incidence screening. (27th October 2010) - Steele, R J C; Kostourou, I; McClements, P; Watling, C; Libby, G; Weller, D; Brewster, D H; Black, R; Carey, F A; Fraser, C
Abstract : Objective To analyse the effects of prevalence and incidence screening on uptake and detection of cancer in an ongoing, dynamic programme for colorectal screening using faecal occult blood testing. Design Analysis of prevalence and incidence screening. Setting Three rounds of biennial colorectal screening using the guaiac faecal occult blood test in east and north east Scotland, March 2000 to May 2007. Participants Adults aged 50-69. Main outcome measures Uptake of screening, test positivity (percentage of those invited who returned a test that was positive and triggered an invitation for colonoscopy), positive predictive value, and stage of cancer. Results Of 510 990 screening episodes in all three rounds, 248 998 (48.7%) were for prevalence, 163 483 (32.0%) were for first incidence, and 98 509 (19.3%) were for second incidence. Uptake of a first invitation for prevalence screening was 53% and for a second and third invitation was 15% and 12%. In the cohort invited for the first round, uptake of prevalence screening rose from 55% in the first round to 63% in the third. The uptake of first incidence screening on a first invitation was 54% and on a second invitation was 86% and on a first invitation for second incidence screening was 46%. The positivity rate in prevalence screening was 1.9% and the uptake of colonoscopy was 87%. The corresponding values for a first incidence screen were 1.7% and 90% and for a second incidence screen were 1.1% and 94.5%. The positive predictive value of a positive faecal occult blood test result for cancer was 11.0% for prevalence screening, 6.5% for the first incidence screen, and 7.5% for the second incidence screen. The corresponding values for the positive predictive value for adenoma were 35.5%, 29.4%, and 26.7%. The proportion of cancers at stage I dropped from 46.5% for prevalence screening to 41% for first incidence screening and 35% for second incidence screening. Conclusions Repeat invitations to those who do not take up the offer of screening increases the number of those who accept, for both prevalence screening and incidence screening. Although the positive predictive value for both cancer and adenomas fell between the prevalence screen and the first incidence screen, they did not fall between the first and second incidence screens. The deterioration in cancer stage from prevalence to incidence screening suggests that some cancers picked up at incidence screening may have been missed on prevalence screening, but the stage distribution is still favourable. These data vindicate the policies of continuing to offer screening to those who fail to participate and continuing to offer biennial screening to those who have accepted previous offers.